Public Statements of Good Conduct Promote Pro-Social Behavior - Ann-Kathrin Koessler; Lionel Page; Uwe Dulleck (SSRN, 2018)
Voluntary and compulsory public statements of good conduct are frequently observed in the real world, such as the codes of good conduct for professionals or the requirements of academic journals to affirm that research was carried out ethically. In this study, we investigate what effect public statements of good conduct have on contribution behavior in a public goods experiment. Using a 'between-within subjects design' we identify three channels by which non-enforceable statements of intent are associated with higher levels of contributions to the public good. First, in a selection effect, socially-oriented participants are more likely in the experiment to make a public statement. Second, in a commitment effect, participants who make a public statement are contributing more to the public good. Third, in a coordination effect, aggregate contributions are higher when 'Statement-Makers' observe that also other group members make the statement. The latter explains why compulsory statements of good conduct are in our experiment more effective over time.
Keywords: A13; C72; C91; H41; 330; social dilemma; public good; pro-social behavior; commitment; compliance; pledges; policy making